A multi-additive suppressant agent–based low-flow and long-distance firefighting approach for suppressing wildfires near electrical transmission lines. (September 2016) - Lu, JiaZheng; Chen, Bao-Hui; Wu, ChuanPing; Liu, Xing; Zhou, TeJun; Tan, YanJun
The key challenges of the wildfire firefighting were long-distanced and high-lifted fire events and limited water access in wildlands. This article proposed a new low-flow and high-lift firefighting approach for the application of wildfire near transmission lines. To solve the challenges, we developed a comprehensive firefighting equipment set which consisted of a high-effective suppressant agent with properties to prevent reignition and a mobile firefighting platform with long-distance and high-lift features. The liquid suppression agent improved the effectiveness of fire suppression while reducing the consumption of water significantly. As the hydraulic flow was decreased for a given volume of water, the hydraulic pressure was increased. In this way, the platform can produce a hydraulic pressure over 120 bar for an effective lift of 500 m. The results of field experiments demonstrated that the proposed approach is able to control wildfires over a long distance and high lift, which proved the effectiveness of the approach.